FORMULASI UNDANG-UNDANG NOMOR 1 TAHUN 1974 DALAM PERSINGGUNGAN ANTARA NEGARA DAN AGAMA - Fenni Febiana (Millah: Journal of Religious Studies, 2017)
With the enactment of Law No. 1 of 1974 on Marriage, the authors noticed that the policy in question is to accommodate the aspirations of the majority Muslims who happen to choose schools of Shafi'i schools and realized in the form of legislation. The hope of course that the values of Islam, which had long color the way of arbitrate Indonesian people, then can have the firmness and recognition from the state. Thus the struggle of Muslims, which in certain portions require the enactment of Islamic law, at least one by one can be realized even with regard to the context Indonesian nation known multi-religious, ethnic and cultural. This is consistent with the theory put forward by the imam, al-Maliki al-mursalah mashlahah which can be translated "public interest". Al-maslahah occupy a very important position in determining the details of the general principles of the constitution in Islam. Through this principle all aspects of society that have not been regulated in the Quran and Sunnah Rasul can be arranged by the man, or the principles of a general nature contained in the Qur'an can be broken down further in order to determine a lot of applications in the life of society and the state extent not inconsistent with the spirit of Islamic law (sharia).